The study of records management policies and procedures in Safeguards Corporation Sdn. Bhd. / Nur Mahirah Maizan... [et al.] - Maizan, Nur Mahirah; Ab. Harith, Aminur Aishah; Omar, Nur Ilani Khairunnisa; Mohamed Nordin, Norhanissa Fazreena (2014)
Records management should be systematic and organize system in dealing with records. It is a process starting from the creation of records until disposal which requires skills and knowledge towards it. The purpose of this research is to analyze the behavioural of employee towards the policies and procedures thus the Safeguard Records Management Department was chosen to determine and identify policies and procedures used and investigate their staff expertise and qualification in this field. The questionnaire was designated and distribution of questionnaires was distributed to the all level of staff. Data were gathered from 57 respondents who came from selected branches and based on the study there are some findings arise in dealing with records management thus the recommendation towards the issues were suggested in this research.